2002
DOI: 10.4269/ajtmh.2002.67.555
|View full text |Cite
|
Sign up to set email alerts
|

Malaria infections are randomly distributed in diverse holoendemic areas of Papua New Guinea.

Abstract: Abstract. Malaria is holoendemic in the lowlands of Papua New Guinea (PNG), and interactions among Plasmodium species may influence prevalence of mixed infections. Previously, field samples from a cross-sectional survey in Dreikikir, East Sepik Province, analyzed by blood smear and polymerase chain reaction (PCR), showed that mixed infections were common and randomly distributed in this malaria endemic region. To evaluate further whether Plasmodium species distribution is random, blood smear-and PCR/sequence-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
71
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 36 publications
8
71
2
Order By: Relevance
“…In a series of studies from PNG that have combined LM and molecular diagnostics [29,31,32], we have found that molecular methods consistently detected significantly increased prevalence of all four malaria species of humans, with the largest increases in P. malariae and P. ovale. In these studies from three different PNG populations, the prevalence of P. falciparum and P. vivax increased between 1.6 and 3.0-fold and 2.1 and 3.4-fold, respectively, and a 2.6 to 10.9-fold increase in P. malariae prevalence was observed (LM:…”
Section: Improved Diagnosis Of P Malariae and P Ovale Infections Bymentioning
confidence: 97%
See 3 more Smart Citations
“…In a series of studies from PNG that have combined LM and molecular diagnostics [29,31,32], we have found that molecular methods consistently detected significantly increased prevalence of all four malaria species of humans, with the largest increases in P. malariae and P. ovale. In these studies from three different PNG populations, the prevalence of P. falciparum and P. vivax increased between 1.6 and 3.0-fold and 2.1 and 3.4-fold, respectively, and a 2.6 to 10.9-fold increase in P. malariae prevalence was observed (LM:…”
Section: Improved Diagnosis Of P Malariae and P Ovale Infections Bymentioning
confidence: 97%
“…Detection of P. ovale by LM ranged from 0 to 0.3%, whereas LDR-FMA detected P. ovale infection in 5.2 to 15.6% of the study subjects. Overall, the majority of P. malariae and P. ovale diagnoses have been observed in the context of mixed infections with P. falciparum and/or P. vivax, including several quadruple infections [29,31,32]. Therefore, it is likely that P. malariae, P. ovale and mixed species infections are substantially more common in PNG than previously thought.…”
Section: Improved Diagnosis Of P Malariae and P Ovale Infections Bymentioning
confidence: 99%
See 2 more Smart Citations
“…All these samples were obtained from the West Atlantic sub-group of the Niger-Congo linguistic group of individuals, implying that all these West African individuals belong to the same ethnicity. Blood samples from PNG (n=153) were collected from the Wosera area of East Sepik Province as a part of the malaria epidemiology study previously described [25]. Samples from PNG were obtained from the Abelam linguistic group of individuals.…”
Section: Methodsmentioning
confidence: 99%